The Effect of Implementing the Problem-Based Learning (PBL) Model Assisted by Wordwall Media in IPAS Learning - Putri, Suci Rahma; Ali, Gunawan; Sari, Kurnia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the low learning outcomes in IPAS (Integrated Science and Social Studies) among students. Therefore, this study aims to determine the effect of implementing the Problem-Based Learning (PBL) model with the help of Wordwall media in IPAS learning on the learning outcomes of fifth-grade students. This research uses a quantitative approach with a quasi-experimental type and a one-group pretest-posttest design. The population of this study consists of all fifth-grade students. The sample was taken using a saturated sampling technique. Data collection was carried out using tests with question instruments. After applying the Problem-Based Learning (PBL) model, the average pretest score was 56, and the posttest score was 72, indicating a higher posttest score. Based on non-parametric statistical analysis, it was found that the asymptotic significance (2-tailed) value was 0.000, which is smaller than 0.50, thus the hypothesis is accepted. This means there is a difference between the pretest and posttest results. Therefore, it can be concluded that the hypothesis stating the influence of applying the Problem-Based Learning (PBL) model with the help of Wordwall media in IPAS learning on the learning outcomes of fifth-grade students is accepted.